KOMUNIKASI DAKWAH ORANG TUA TERHADAP REMAJA DALAM PELAKSANAKAN SHALAT LIMA WAKTU - Harahap, Sahdani (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
Some of the ways that families do in building children's character include building honesty, instilling religious values, sincerity in worship, activities, caring for others and togetherness, parents have an obligation to teach prayer, guide and train them to be diligent in praying and must be able to provide encouragement The child wants to pray as well as possible in his life. The research method used is descriptive qualitative. Communication patterns in the implementation of the five daily prayers, interpersonal communication patterns of parents have communicated with teenagers in carrying out the prayers. But there are also teenagers who do not care about and even ignore the orders of their parents in carrying out the prayers. But there are also teenagers who pray without being told.